Stash and smash - Shepard, Cindy (Design Originals, 2011)
A Stash Book is a place to store memorabilia, scraps of stuff to use in later art projects, and most importantly, to record those jolts of inspiration that you don't have time to work out right now. Jot down your creative insights and they will be waiting in your book. As you fill your pages, your book becomes a record of your artistic endeavors and interests. You'll have memories of a personal artistic journey in a format that's fun to share with family and friends. Stash and Smash shows how to make your own journal books, embellish the pages, organize with tabs, flaps, envelopes, and pockets full of fun ideas. Over 100 ideas are waiting to fuel your imagination, energize your creativity, and encourage you to get started.